2006
DOI: 10.1002/cbic.200600277
|View full text |Cite
|
Sign up to set email alerts
|

Factors Mediating Activity, Selectivity, and Substrate Specificity for the Thiamin Diphosphate‐Dependent Enzymes Benzaldehyde Lyase and Benzoylformate Decarboxylase

Abstract: Benzaldehyde lyase from Pseudomonas fluorescens and benzoylformate decarboxylase from Pseudomonas putida are homologous thiamin diphosphate-dependent enzymes that catalyze carboligase and carbolyase reactions. Both enzymes catalyze the formation of chiral 2-hydroxy ketones from aldehydes. However, the reverse reaction has only been observed with benzaldehyde lyase. Whereas benzaldehyde lyase is strictly R specific, the stereoselectivity of benzoylformate decarboxylase from P. putida is dependent on the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 30 publications
3
115
0
2
Order By: Relevance
“…BAL is a very active catalyst that is able to form and also to cleave chiral hydroxy ketones. Other ThDP-dependent enzymes, such as BFD, are not able to perform this cleavage due to steric hindrance (Knoll et al, 2006). Therefore, in order to fit the derived kinetic model, BAL is chosen.…”
Section: Comparison Of Computer Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…BAL is a very active catalyst that is able to form and also to cleave chiral hydroxy ketones. Other ThDP-dependent enzymes, such as BFD, are not able to perform this cleavage due to steric hindrance (Knoll et al, 2006). Therefore, in order to fit the derived kinetic model, BAL is chosen.…”
Section: Comparison Of Computer Programsmentioning
confidence: 99%
“…Structural studies from Knoll et al (2006) show that the active site of BAL is partly covered by a C-terminal helix, whereas in BFD H281A such a structural element is absent (Figure 2-26).…”
Section: Figure 2-25mentioning
confidence: 99%
“…PpBFD is S selective for the formation of 2-HPP, but R selective with acceptors larger than acetaldehyde. [30] Despite their low sequence similarity, all decarboxylases have a conserved active site architecture. Therefore, it was challenging to identify the molecular basis of the differences in stereoselectivity and to establish a general rule to predict and engineer substrate specificity and selectivity Scheme 2.…”
Section: Case Study 1: Engineering the Regioselectivity Of Cytochromementioning
confidence: 99%
“…By a detailed comparison of the substrate binding sites of PpBFD (PDB entry 1MCZ) and of PfBAL (PDB entry 1AG0) and a manual docking of donor and acceptor substrates, it was demonstrated that the size of the acceptor binding site in both enzymes differs, and a mechanistic model to explain stereoselectivity was suggested. [30] The acceptor molecule is assumed to bind in either of two possible orientations relative to the donor molecule, parallel or antiparallel (Figure 3). These two orientations result in (R)-or (S)-a-hydroxy ketones, respectively.…”
Section: Case Study 1: Engineering the Regioselectivity Of Cytochromementioning
confidence: 99%
“…[10] The structural reasons for the differences in selectivity have recently been elucidated. [11] So far both enzymes have been applied in synthetic processes as free enzymes by the addition of ThDP and Mg 2+ as cofactors to the reaction buffer, in order to keep the holo-enzymes stable. The substrate and product concentrations were usually in the range of 20-50 mM.…”
Section: Introductionmentioning
confidence: 99%